2014
DOI: 10.3109/00365513.2014.981855
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term outcome after acute myocardial infarction using circulating miR-145

Abstract: Circulating miR-145 may be a novel biomarker for predicting long-term outcome after acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…As miR-145 is reported as a biomarker for MI [32], we explored the alteration of miR-145 in H9c2 cells under hypoxia. The results showed that miR-145 was up-regulated, suggesting the possible involvement of miR-145 in hypoxia-induced injury of H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…As miR-145 is reported as a biomarker for MI [32], we explored the alteration of miR-145 in H9c2 cells under hypoxia. The results showed that miR-145 was up-regulated, suggesting the possible involvement of miR-145 in hypoxia-induced injury of H9c2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The seven selected studies 22,23,27,28,30,35,36 ( Table 5 ) did not identify miRs which significantly predicted long-term mortality; however, mid-term and short-term mortality could be predicted to a certain extent. …”
Section: Resultsmentioning
confidence: 96%
“…22 1053 (−); 102(+) a miR-133a, miR-208b, miR-223, miR-320a, miR-451, miR-499miR-208b (+)Unadjusted ROC (AUC: 95% CI) a :0.67: 0.52–0.81Dong et al . 23 224(−); 22(+) b miR-145miR-145 (+)Multivariate Cox regression(HR: 95% CI) b, c :5.63: 1.99–15.91, P = 0.0012Goretti et al . 27 446(−); 64(+) d miR-208b, miR-499Multivariate linear regression d : ORs and 95% CI include 1He et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…miR‐150 limits atherogenesis by moderating immune cell activation and secretion of cytokines and enhances vascular health by promoting endothelial and endothelial progenitor cell function (Desjarlais, Dussault, Dhahri, Mathieu, & Rivard, ). Lower circulating levels of miR‐145 and miR‐150 have been linked with increased CVD risk and events (Dong et al., ; Rhodes et al., ). The lack of alteration in these miRNAs with insufficient sleep suggests a differential effect of sleep on circulating miRNA and demonstrates the complexity of the interaction of sleep and circadian physiology with miRNA regulation and, in turn, cellular function.…”
Section: Discussionmentioning
confidence: 99%